Is military spending quantitatively important for business cycle fluctuations in Bulgaria - Aleksandar Vasilev (Economics and Econometrics Research Institute (EERI), 2021)
We introduce a military sector and external security considerations into a real-businesscycle setup with a public sector. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2018). We investigate the quantitative importance of the presence of a military sector and external threat considerations for the cyclical fluctuations in Bulgaria. We find the quantitative effect of such aspects to be very small, and thus not important for business cycle stabilization, or public finance issues, as in Bulgaria the spending on military is relatively small relative to the size of the economy.
Keywords: E24; E32; 330; business cycles; military spending; security considerations; external threats; Bulgaria